The Effect of Guessing Picture Application on the Students’ Vocabulary Mastery of 7th Graders at SMPN 1 Plosoklaten - Umi Fatkurohmah; Ima Fitriyah; Renita Donasari (JALL (Journal of Applied Linguistics and Literacy), 2023)
Vocabulary is important in English because it is the main capital for learning various skills in a language. Therefore, teaching techniques are needed to teach vocabulary appropriately. Teaching vocabulary can be done easily through descriptive text because students will produce a lot of vocabulary to describe something. Moreover, interesting and creative teaching media uses technology will help the teaching of descriptive text, namely Guessing Picture Application. The purpose of this study is to find out the effect of Guessing Picture Application in the students' vocabulary mastery of 7th graders at SMPN 1 Plosoklaten. This research used quantitative approach of research method by using quasi-experimental design, Guessing Picture Application to teach vocabulary in experimental class and Guessing Game to teach vocabulary in control class. The data collection used three steps, namely pre-test, treatments, post-test. Then, the researcher found the result of students’ achievement after they were taught by Guessing Picture Application or Guessing Game (Guessing Picture without Application). This research used ANCOVA in SPSS to analyze the data. The results of this study showed that the significance was 0.014. It was less than 0.05 (0.014 < 0.05). It means this study found a significant difference between students who were taught using Guessing Picture Application and students who were taught by Guessing Game. Therefore, it could be concluded that Guessing Picture Application effectively used in teaching vocabulary since the student could memorize vocabulary better than by using Guessing Game, especially in teaching descriptive text for the seventh-grade students of SMPN 1 Plosoklaten.